Quality analysis of bottled drinking water in Jaffna Peninsula - Ragila, K.; Abiman, P.; Thavaranjit, A.C.; Iyngaran, P. (Faculty of Science, University of Jaffna, 2021)
In Jaffna peninsula ground water was used for drinking and other domestic purposes for long time. However, now this trend is changed and people feel only bottled water is suitable for drinking purposes. Water bottles of five different batch numbers of eight brands were tested for chemical, physical and microbial parameters. The pH of all the water samples studied ranged from 6.06-7.43. The alkalinity of the water samples reflects the same. Conductivity, alkalinity, calcium, magnesium, hardness, potassium, phosphate, chloride, salinity, coliforms and fecal coliforms of the above water samples were determined. The amount of conductivity, alkalinity, calcium, magnesium, hardness, potassium, chloride and salinity were found to be within the Sri Lankan Standard (SLS) recommended values. Phosphate values exceeded the SLS recommended values in tested three bottles. The microbial values revealed that four brands out of eight brands tested, not suitable for drinking purposes. When all the chemical physical and microbial parameters are concerned, only two out of eight brands tested were found to be suitable for drinking purposes.
Keywords: Drinking water; pH; coliforms; SLS